ANALISIS LABEL, INFORMASI NILAI GIZI, KANDUNGAN GIZI, DAN KLAIM GIZI PADA PRODUK MP-ASI KOMERSIAL - Soctmada, Dycco Nur; Suwita, I Komang; Pudjirahaju, Astutik (Poltekkes Kemenkes Malang, 2025)
In Indonesiam there are still discrepancies in labels, nutritional value information (NVI), nutrient content and nutritional claims found in processed food products from several studies that have been conducted, including commercial complementary foods. This research aims to analyze the suitability of nutritional labels, the suitability of nutritional value information, the suitability of nutritional substances, and the suitability of nutritional claims on commercial complementary foods product packaging in overcoming the acceleration of stunting reduction in toddlers. The type of research used is exploratory using a descriptive-qualitative method design by collecting the necessary data from commercial complementary foods product packaging labels, then it is described in its entirety and an overview is given regarding conformity to the label, inclusion of NVI, nutritional content, and nutritional claims. based on existing laws and regulations in Indonesia. A discrepancy was found in the product label for the minimum information category (list of ingredients used) and other information (product designation); The inclusion of NVI is in accordance with the standards; Discrepancies were found in protein content, several vitamins and minerals; Discrepancies were found in claims for iron sources and protein sources; Several violations were found regarding label suitability, nutritional content, and nutritional claims based on Law No. 1 Year 1999 regarding Consumer Protection. There are still discrepancies found in labeling, some nutritional content based on standards, and nutritional claims for iron sources and nutritional claims for protein sources.